Superstability of Some Pexider-Type Functional Equation. (20th October 2010) - Kim, Gwang Hui
Abstract : We will investigate the superstability of the sine functional equation from the following Pexider-type functional equationf ( x + y ) + g ( x − y ) = λ · h ( x ) k ( y ) (λ : constant ), which can be considered the mixed functional equation of the sine and cosine functions, the mixed functional equation of the hyperbolic sine and hyperbolic cosine functions, and the exponential-type functional equations.